ANALISIS PRODUKSI TEMBAKAU RAJANGAN TIPE MAGELANGAN DALAM POLA KEMITRAAN CV. MERABU - PT. DJARUM KUDUS - Sumartono, Eko (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
Purpose of this research is estimate level of input usage; production rate and level of productivity, and to determinefactors influence produce of to produce and productivity at tobacco type rajangan public people type Magelangan. This research applies a descriptive method and multiple regresiion analysis. Result of research indicates that level of input usage, production rate and level of productivity, quality of tobacco type Magelangan has experienced a drastic degradation from the year 2005 to 2009. Hereinafter level of input usage experiences upsurge, although some inputs still experience a degradation. Land area, Ortheen/Roteen 75 SP, Year of 2006, Year of 2007 and Year of 2008 are significant factors affecting production while number of partnership member, NPK Fertil/Basal, Ortheen/Roteen 75 SP, Marcis, Year of 2006, Year of 2007 and Year of 2008 as well as year 0f 2009 are important factors to affect productivity.